Genome-wide identification and expression analysis of Phenylalanine Ammonia-Lyase (PAL) in cucumber - Jiaojiao Zhang; Kunyang Wang; Shuai Meng; Qiushuang Han; Ming Gao (PLoS ONE, 2025)
Phenylalanine ammonia-lyase (PAL) is the key catalytic enzyme that initiates the phenylpropanoid metabolic pathway. This study identified 13 members of the cucumber PAL family to elucidate their characteristics and their potential role in the development of cucumber fruit astringency. All identified members exhibited high conservation and contained three conserved domains: the MIO domain, the core domain, and the insertion shielding domain. Evolutionary pressure selection analysis suggested that purifying selection was the primary driving force behind the evolution of PAL family members. Cis -acting element analysis demonstrated that CsaPALs responded to light, hormones, and stress. Collinearity analysis revealed collinear relationships between AtPAL2 and CsaPAL2 , as well as between AtPAL4 and CsaPAL8 . Transcriptome sequencing exhibited significant differences in the expression levels of CsaPALs between high- and low-astringency cucumber fruits. Furthermore, qRT-PCR analysis revealed that CsaPAL1 , CsaPAL2 , CsaPAL3 , CsaPAL9 , CsaPAL12 , and CsaPAL13 were significantly differentially expressed between the high- and low-astringency fruits, indicating that these genes might serve as candidates for regulating astringency in cucumber. The expression levels of these six genes were also significantly correlated with cucumber fruit tannin content. Overall, these findings provide a solid foundation for further studies on the biological roles of PALs in cucumber.